A Compact Penta-Band Low-SAR Antenna Loaded with Split-Ring Resonator for Mobile Applications. (30th December 2022) - Manikandan, M.; Karthigai Lakshmi, S.
Abstract : A compact rectangular patch with dual-ring SRR (split-ring resonator) is presented in this article. An antenna is designed on FR4 substrate with an overall footprint size of 26 mm × 30 mm × 1.6 mm. The antenna presented operates in five bands from 2.95 to 3.06 GHz, 3.79 to 3.87 GHz, 4.11 to 4.19 GHz, 5.39 to 5.51 GHz, and 5.97 to 6.11 GHz. Mobile and fixed voice communication, WiMAX (Worldwide Interoperability for Microwave Access), 5G (5 th generation), WLAN (Wireless Local Area Network), and ISM (Industrial Scientific and Medical) are some applications that utilized the above resonating bands. The penta-band operation is due to the inclusion of dual-ring SRR. The optimum values of the critical parameter of the SRR are identified using parametric analysis, and the results are presented. The antenna is also analyzed for the SAR (specific absorption rate) values, and it was found to be less than 2 W/kg for 10 g volume of tissue. The designed antenna is fabricated and tested, and the presented results show that there is good agreement between the simulated and measured results. Penta-band operation with simple structure, stable radiation pattern, and low SAR makes this antenna more intelligent and suitable for the mobile application.